Qualitative Analysis of the UK University Spin-Out Company Formation and Early Development Process - Igata, Eishi (2005)
Based upon the Triple-Helix model of university-industry interaction, this study investigates the technology-based university spin-out companies and the assistance being provided by other stakeholders. The research reveals that the spin-out strategy of the university and the practical assistance by the university are the significant factors of the spin-out companies financial performance.